Learning Environment Perceptions, Motivation, and Academic Performance among Nursing Students: A Cross-Sectional Study - Rezki Yeti Yusra; Mutiara Pebriani (Jompa Research and Development, 2026)
Motivation plays an important role in nursing students’ academic success; however, its relationship with the learning environment remains complex. This study examined the relationships among nursing students’ perceptions of the learning environment, motivation to become a nurse, and grade point average (GPA). A cross-sectional study was conducted among 143 nursing students using questionnaires to assess perceptions of the learning environment and motivation, along with documented GPA records. Multiple linear regression analysis was performed. Students’ perceptions of the learning environment explained 37.8% of the variance in motivation to become a nurse (R² = 0.378, p < 0.001), although perceptions of lecturers showed the largest regression coefficient, the association was not statistically significant(p = 0.052). Motivation to become a nurse significantly predicted GPA (R² = 0.116, p < 0.001), while perceptions of the learning environment were not directly associated with GPA. These findings suggest that motivation may play an important role in linking students’ learning environment perceptions with academic performance. The results highlight.